PERANCANGAN SISTEM PEMESANAN ONLINE UNTUK USAHA KALUNA BERBASIS WEB DESIGN MENGGUNAKAN METODE DESIGN THINKING - Atthia Rizki Wisista; Ruly Dwi Arista; Hermansyah (CV. Hawari, 2025)
Kaluna is a product of a MSME operating in the contemporary beverage industry, specifically bubble tea or boba-based drinks. This business offers a variety of flavors, such as taro, cookies 'n' cream, matcha, strawberry biscotis, purple crumb, silverqueen, lava milo, apple tea, and others. The diverse menu and flavors offered make boba drinks consistently appealing to consumers. This research used UI/UX methods with a design thinking approach, encompassing five stages: empathize, define, ideate, prototype, and test. Data was collected through observation and questionnaires with app users to explore their needs, concerns, and preferences. The design results showed that the web application prototype was able to effectively display the decoration catalog, simplify the ordering process, and facilitate customer service confirmation.